Risk of ischaemic heart disease in patients with inflammatory bowel disease: a nationwide Danish cohort study. Issue 5 (8th September 2012) - Rungoe, Christine; Basit, Saima; Ranthe, Mattis Flyvholm; Wohlfahrt, Jan; Langholz, Ebbe; Jess, Tine
Abstract : Background: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder. Systemic inflammation increases the risk of atherosclerosis and ischaemic heart disease (IHD). Objective: To examine the impact of IBD, including its duration and treatment, on the risk of IHD. Methods: In a nationwide population-based cohort of 4.6 million Danes aged ≥15 years, we compared people diagnosed with IBD during 1997–2009 (n=28 833) with IBD-free individuals. Subjects with IHD were identified in the National Patient Register. Using Poisson regression, we estimated the incidence rate ratios (IRRs) for IHD with 95% CI with adjustment for age, gender, socioeconomic status, calendar year and use of drugs for comorbidities. Results: A markedly increased risk of IHD was seen within the first year after IBD diagnosis (IRR=2.13 95% CI 1.91 to 2.38). During 1–13 years of follow-up after IBD diagnosis, the risk of IHD was 1.22 (95% CI 1.14 to 1.30). The risk of IHD was lower among patients with IBD using 5-aminosalicylic acids (IRR=1.16; 95% CI 1.06 to 1.26) than among non-users (IRR=1.36; 95% CI 1.22 to 1.51) (p=0.02), in particular among oral corticosteroid users, used as a proxy for disease severity. Likewise patients treated surgically or with thiopurines and tumour necrosis factor α antagonists tended to have reduced IRRs for IHD. Conclusions: The risk of IHD was highest in the first year after IBD diagnosis, possibly owing to ascertainment bias. The increased long-term risk of IHD in IBD may be related to chronic inflammation, and interventions reducing the inflammatory burden may attenuate this risk.